Hubungan Pengetahuan Dan Sikap Tenaga Kesehatan Terhadap Perilaku Pemisahan Sampah Medis di RSUD Dr. A. Dadi Tjokrodipo Bandar Lampung - Monica Ramadayanti, Desty; Dwi Nuryani, Dina; Amirus, Khoidar; Riyanti, Riyanti (Jurnal Ilmiah Manusia Dan Kesehatan, 2024)
The potential hazard in medical waste starts from the process of sorting, collecting, storing, transporting, disposing to destruction. WHO estimates that around 1.67 million cases of hepatitis B, 315,120 cases of hepatitis C, and 33,877 cases of HIV are caused by unsafe needles and improper medical waste disposal systems. In addition, staff who handle medical waste are at risk of contracting AIDS, skin infections, anthrax, meningitis, dengue fever, bacteremia, and candidemia. The aim of the research is to know the relationship between knowledge and attitudes of health workers towards medical waste separation behavior. This research is a quantitative type with a cross sectional design with a total population of 253 health workers and a sample of 60 respondents. The sampling technique used was purposive sampling and used univariate and bivariate analysis with statistical tests using the Chi Square test. Respondents who had bad knowledge regarding the separation of medical waste were 46.7% and those who had a negative attitude were 80.8% and those who had bad behavior were 56.7%. There is a relationship between the knowledge of health workers (p-value = 0.007) and OR 4,385 (1,447 – 13,288) and there is a relationship between the attitudes of health workers (p-value = 0.001) and OR 6,785 (2,052 – 22,429) on the behavior of separating medical waste. It is hoped that there will be a need for supervision of the separation of medical waste so that the implementation of the SOP can be implemented correctly. Keywords: Knowledge, Behavior and Attitudes